The transverse and vertical distribution of prostate cancer in biopsy and radical prostatectomy specimens - Mai, Zhipeng; Zhou, Zhien; Yan, Weigang; Xiao, Yu; Zhou, Yi; Liang, Zhiyong; Ji, Zhigang; Li, Hanzhong (BMC cancer, 2018)
Prostate biopsy is the most common method for the diagnosis of prostate cancer and the basis for further treatment. Confirmation using radical prostatectomy specimens is the most reliable method for verifying the accuracy of template-guided transperineal prostate biopsy. The study aimed to reveal the spatial distribution of prostate cancer in template-guided transperineal saturation biopsy and radical prostatectomy specimens. Between December 2012 to December 2016, 171 patients were diagnosed with prostate cancer via template-guided transperineal prostate biopsy and subsequently underwent laparoscopic radical prostatectomy. The spatial distributions of prostate cancer were analyzed and the consistency of the tumor distribution between biopsy and radical prostatectomy specimens were compared. The positive rate of biopsy in the apex region was significantly higher than that of the other biopsy regions (43% vs 28%, P < 0.01). In radical prostatectomy specimens, the positive rate was highest at the region 0.9-1.3 cm above the apex, and it had a tendency to decrease towards the base. There was a significant difference in the positive rate between the cephalic and caudal half of the prostate (68% vs 99%, P < 0.01). There were no significant differences between the anterior and posterior zones for either biopsy or radical prostatectomy specimens. The tumor spatial distribution generated by template-guided transperineal prostate biopsy was consistent with that of radical prostatectomy specimens in general. The positive rate was consistent between anterior and posterior zones. The caudal half of the prostate, especially the vicinity of the apex, was the frequently occurred site of the tumor.